Effectivity of Aroma, Light, and Al'Quran Therapy to Enhance Driver's Level of Awareness in Malaysia - Kurniawan, Yohan (ANIMA Indonesian Psychological Journal, 2010)
The effectiveness of fatigue therapy toward drivers was measured with three treatments using an aroma therapy (the odor of lemon, cananga and stinking egg), sparkling lights therapy and Al ‘Quran therapy. This repetitive experiment design was done in a driving simulator. The level of fatigue was measured using a fatigue questionnaire. The drivers (N = 20 males) were asked to stop their driving when they got tired, and the result shows that the driving duration was shorter when the stinking egg therapy was given compared to the other therapy treatments. Driving period by using Quran therapy was longer than aroma therapy and the sparkling light therapy. The therapy of stinking odor strongly stimulates the sleepy driver to awaken compared to the other treatments. The therapy of listening to Al ‘Quran passages increased persistence and keep the drivers to be awake when they took a long drive compared to the other treatments. Efektivitas terapi kelelahan pada pengemudi diukur dengan tiga jenis perlakuan, berupa terapi aroma (bau limau, kenanga, dan bau telur busuk), terapi lampu kerlip, dan terapi bacaan Al ‘Quran. Penelitian dengan desain eksperimen berulang ini dilakukan dalam simulator mengemudi. Tingkat keletihan subjektif diukur dengan angket keletihan. Para pengemudi (N = 20 pria) diminta berhenti bila telah merasa lelah. Hasil menunjukkan waktu mengemudi lebih singkat bila diberi bau telur busuk dibanding bau limau, kenanga, dan kerlipan lampu, serta bacaan Al ’Quran. Waktu mengemudi dengan terapi bacaan Al’Quran lebih lama dibandingkan ketika mendapat terapi aroma dan terapi lampu kerlip. Perlakuan bau busuk lebih cepat menyadarkan pengemudi yang mengantuk dibandingkan perlakuan bau limau, bau kenanga, lampu kerlip, dan bacaan Al’Quran. Perlakuan bacaan Al’Quran dapat meningkatkan ketahanan dan menjaga kesadaran pengemudi ketika mengemudi dalam waktu lama dibandingkan perlakuan bau limau, bau kenanga, bau busuk, dan perlakuan lampu kerlip.